Experiment study on the performance of the tri-mode thermosiphon beam - Fedi (Nanyang Technological University, 2021)
Thermosiphon beams is part of the integrated system of Air conditioning and Mechanical Ventila tion (ACMV) The main objective of an ACMV thermosiphon beam is to provide environmental comfort without having to consume a lot of energy in a cl osed spaced environment. In the past, one o f technologies of ACMV system include the active chilled beam to pr ovide thermal comfort, however the major drawback of such system was the huge number of energy requirement of the building and such technology has limited pe rformance in hot and humid regio n countries. Hence in order to overcome such drawback, group of eng ineer and scientist from the top University at Nanyang Technological University has developed new technology which potentially able to provide the rmal comfor t while maintaining the cos t and energy building consumption. The new technology is known as Tri Mo de Thermosiphon Beam (TMTB) and this thesis describes the basic phenomena, experimental setup and detailed working principal of TMTB. It consists of the test that were conducted at Ene rgy R esearch Institute Lab at NTU , and the raw data were measured by hig h accuracy sensis devices and logged and represented in BSTAR. The result are validated with appropriate graphical representation